Paediatric pancreaticobiliary endoscopy: a 21-year experience from a tertiary hepatobiliary centre and systematic literature review - Margaret G. Keane; Mayur Kumar; Natascha Cieplik; Douglas Thorburn; Gavin J. Johnson; George J. Webster; Michael H. Chapman; Keith J. Lindley; Stephen P. Pereira (BMC, 2018)
Abstract Background In adults ERCP and endoscopic ultrasound (EUS) are standard methods of evaluating and treating many hepatopancreaticobiliary (HPB) conditions. HPB disease is being diagnosed with increasing frequency in children but information about role of ERCP and EUS and their outcomes in this population remain limited. Therefore the aims of this study were to describe the paediatric ERCP and EUS experience from a large tertiary referral HPB centre, and to systematically compare outcomes with those of other published series. Methods All patients <18 years undergoing an ERCP or EUS between January 1992-December 2014 were included. Indications for the procedure, rates of technical success, procedural adverse events and reinterventions were recorded in all cases. Results Ninety children underwent 111 procedures (87 ERCPs and 24 EUS). 53% (48) were female with a median age of 14 years (range: 3 months - 17 years). Procedures were performed under general anaesthesia (n = 48) or conscious sedation (n = 63). Common indications for ERCP included chronic or recurrent pancreatitis and biliary obstruction. Patients frequently had multiple comorbidities, with a median ASA grade of 2 (range 1-4). Therapeutic procedures performed included biliary or pancreatic sphincterotomy, common bile duct or pancreatic duct stone removal, biliary or pancreatic stent insertion, EUS-guided fine needle aspiration and endoscopic transmural drainage of pancreatic fluid collections. No adverse events were reported following ERCP but there was one complication requiring surgery following EUS guided cystenterostomy. Conclusion ERCP and EUS in children and adolescents have high technical success rates and low rates of adverse events when performed in high volume HPB centres.